The Effectiveness Of Verapamil And Dıgitalis In Recent Onset Supraventricular Tachycardias - Kadikoylu, Gurhan; Cicek, Ceyhan; Akar, Harun; Yavasoglu, Irfan; Senturk, Taskin; Bolaman, Zahit (Annals of Medical Research, 2021)
None
Keywords: Supraventricular tachycardias, Digitalis, Verapamil